Inhibitory Receptor Signaling Destabilizes Immunological Synapse Formation in Primary NK Cells - Abeyweera, Thushara P.; Huse, Morgan; Kaissar, Molly (Frontiers in Immunology, 2013)
Upon engagement of their cognate class I major histocompatibility complex (MHC) ligands, receptors containing immunotyrosine-based inhibitory motifs (ITIMs) transduce signals that block cytolytic and inflammatory responses. In this manner, ITIM-coupled receptors play a crucial role in maintaining natural killer (NK) cell tolerance toward normal, healthy tissue. A number of studies, mostly using immortalized NK cell lines, have demonstrated that ITIM signaling functions by disrupting the cytolytic immunological synapse formed between an NK cell and its target. However, more recent imaging experiments using primary NK cells have suggested that inhibitory receptor engagement does not antagonize contact formation, casting doubt on the hypothesis that ITIM signals destabilize the synapse. To resolve this issue, we analyzed primary NK cell activation and contact formation on supported lipid bilayers containing controlled combinations of activating and inhibitory ligands. Under these conditions, we observed that ITIM signaling clearly inhibited adhesion, cell arrest, and calcium influx, three hallmarks of synapse formation. These results are consistent with previous reports showing that inhibitory receptors deliver a “reverse stop” signal, and confirm that ITIM signaling functions at least in part by destabilizing cytolytic synapse formation.